Leadership Development: Leadership Emergence to Leadership Effectiveness. (October 2019) - Luria, Gil; Kahana, Allon; Goldenberg, Judith; Noam, Yair
This study aimed to understand how leadership effectiveness of the trainer in a leadership development program can influence emerging leaders' development and effectiveness. We hypothesized that the trainer's leadership effectiveness would be a boundary condition. In this two year longitudinal field study, military cadets' leadership effectiveness from their emergence as informal peer leaders during basic training through the officer training course (OTC) to their formal leadership roles as active duty officers was followed. The sample included 854 cadets and their 72 trainers. We found that cadets' effectiveness during OTC mediated the relationship between informal leadership emergence during basic training and their subsequent effectiveness as formal leaders. Furthermore, trainers' effectiveness moderated the relationship between cadets' informal leadership emergence and effectiveness in OTC. Results indicate that informal emerging leaders are more likely to develop into highly effective formal leaders when supervised by effective trainers. Theoretical and applied implications are discussed.